Conjunctivitis in atopic dermatitis patients with and without dupilumab therapy – international eczema council survey and opinion. (6th May 2019) - Thyssen, J.P.; de Bruin‐Weller, M.S.; Paller, A.S.; Leshem, Y.A.; Vestergaard, C.; Deleuran, M.; Drucker, A.M.; Foelster‐Holst, R.; Traidl‐Hoffmann, C.; Eyerich, K.; Taieb, A.; Su, J.C.; et al.
Abstract: Background: Conjunctivitis is common in patients with atopic dermatitis (AD) in general and a commonly reported adverse event in AD clinical trials with dupilumab. Objective: To survey opinions and experience about conjunctivitis occurring in AD, including those during dupilumab treatment in a group of AD experts from the International Eczema Council (IEC). Methods: Electronic survey and in‐person discussion of management strategies. Results: Forty‐six (53.5%) IEC members from 19 countries responded to the survey. Consensus was reached for several statements regarding diagnostic workup, referral and treatment. IEC members suggest that patients with AD should (i) routinely be asked about ocular complaints or symptoms, (ii) obtain information about the potential for conjunctivitis before starting dupilumab therapy and (iii) if indicated, be treated with dupilumab despite previous or current conjunctivitis. In cases of new‐onset conjunctivitis, there was consensus that dupilumab treatment should be continued when possible, with appropriate referral to an ophthalmologist. Limitations: The study relies on expert opinion from dermatologists. Responses from few dermatologists without dupilumab access were not excluded from the survey. Conclusion: The IEC recommends that dermatologists address conjunctivitis in patients with AD, especially during treatment with dupilumab.